Left atrial anatomical variations correlate with atrial fibrillation sources near the left atrial ridge - Gagyi, Rita B.; Szegedi, Nándor; Simon, Judit; Wijchers, Sip; Bhagwandien, Rohit; Kong, Melissa H.; Ruppersberg, Peter; Szili-Torok, Tamas (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Anatomical variations and characteristics of the left atrium (LA) may have a previously undescribed effect on source locations in atrial fibrillation (AF). This is the first study aiming to investigate the relationship between anatomical characteristics of the LA and non-PV sources detected by electrographic flow (EGF) mapping in patients with persistent AF. Methods: We analyzed cardiac computed tomography (CT) and EGF mapping data in patients who underwent radiofrequency catheter ablation (CA). EGF mapping is a novel method based on Horn-Schunk flow estimation algorithm, used to estimate cardiac action potential flow in the atria that can detect AF sources in patients with persistent AF. By analyzing EGF maps obtained during CA procedures, we localized non-PV sources in the LA. Results: Thirty patients were included in this study (mean age 62.4 ± 6.8 years). Ten patients had AF sources near the LA ridge, while twenty patients had no leading source (source activity > 26%) near the LA ridge. LA anatomical characteristics, left atrial appendage (LAA) length and ostial diameter showed no correlation with the presence of a leading source. We documented 19 patients with abutting LAA and left superior pulmonary vein (LSPV) (distance < 2 mm), and 11 patients with non-abutting LAA-LSPV (distance > 2 mm). Three out of 19 patients presented with a leading source near ridge in the abutting LAA-LSPV group, while 7 out of 11 patients presented with a leading source near ridge in the non-abutting LAA-LSPV group (p = 0.01). Conclusion: Our data suggests that non-abutting LAA-LSPV is associated with the presence of AF sources near the LA ridge.